1906 San Francisco earthquake - Cooke, Tim (Milwaukee : Gareth Stevens Pub., 2005)
Describes the events that cause an earthquake, the devastation it can cause, and the lessons learned from such a tragedy.
7 - 10 years
86642
Keywords: San Francisco Earthquake, California -- 1906; Earthquakes -- California -- San Francisco; San Francisco Earthquake, California -- 1906; Earthquakes -- California -- San Francisco